Black Mirror: White Christmas - Tibbetts, Carl; Steel, George; Hamm, Jon; Spall, Rafe; Chaplin, Oona (Channel 4, 2015)
"Black Mirror: White Christmas" is a chilling feature-length seasonal special of the critically-acclaimed drama series, starring Jon Hamm, Rafe Spall and Oona Chaplin. And it's the most mind-bending episode yet, consisting of three interwoven stories brimming with near-future madness. In a mysterious and remote snowy outpost, Matt (Jon Hamm) and Potter (Rafe Spall), share a Christmas meal together and swap creepy tales of their earlier lives in the outside world. Matt is a charismatic American trying to bring the reserved, secretive Potter out of his shell. Are both men who they appear to be? Along the way we see Matt offering an unusual form of romantic guidance to an inexperienced young man, watch Great (Oona Chaplin) thrust headlong into a nightmarish world of ‘smart' gadgetry, and explore what might happen if you could 'block' people in real life, just as you can on Facebook or Twitter. All three stories are bound together into a suitably unsettling whole. Fans of eerie Christmas stories are in for a treat ... [Cover]
Keywords: DVD-Video